Effect of Intensity on Changes in Cardiac Autonomic Control of Heart Rate and Arterial Stiffness After Equated Continuous Running Training Programs - Soltani, Mohammad; Baluchi, Masoud Jokar; Boullosa, Daniel; Daraei, Ali; Doyle-Baker, Patricia K.; Saeidi, Ayoub; Knechtle, Beat; Dehbaghi, Kambiz Moradi; Mollabashi, Shirin Shirzad; VanDusseldorp, Trisha A.; Zouhal, Hassane (Frontiers in Physiology, 2021)
Background: It is well known that exercise training has positive effects on both cardiac autonomic function and arterial stiffness. However, it is not clear which exercise training variables, intensity, or volume, or both, play a crucial role in this regard. The current study investigated the chronic effects of high-volume moderate-intensity training (HVMIT) and low-volume high-intensity training (LVHIT) on heart rate variability (HRV) and arterial stiffness in sedentary adult men. Materials and methods: Forty-five males (age: 42 ± 5.7 yrs.) were randomly assigned to a control (n=15), HVMIT (n=15), or LVHIT (n=15). The HVMIT group ran three times per week on a treadmill at 50% to 60% of VO2max for 45 to 60 minutes, while the LVHIT trained at 70% to 85% of VO2max for 25 to 40 minutes. Both training protocols were equated by caloric expenditure. HRV, pulse wave velocity (PWV), hemodynamic variables, and body composition were measured before and after 12 weeks. Results: Both protocols (HVMIT and LVHIT) significantly increased the standard deviation of normal sinus beats intervals (SDNN) and high-frequency (HF) bands (p ˂ 0.05) after 12 weeks. Whereas the low-frequency (LF)/HF ratio decreased significantly in both training protocols (p ˂ 0.05) however, these changes were significantly greater in the LVHIT protocol (p ˂ 0.05). Furthermore, the root mean square of successive RR interval differences (RMSSD) significantly increased only in the LVHIT (p ˂ 0.05). Moreover, a significant decrease in LF and PWV was only observed following the LVHIT protocol (p ˂ 0.05). Some measures of HRV and PWV were significantly correlated (r=0.275-0.559; p<0.05). Conclusion: These results show that the LVHIT protocol was more efficient for improving HRV variables and PWV than the HVMIT protocol after 12 weeks of continuous running training. Interestingly, changes in some HRV parameters were related to changes in PWV. Further studies should elaborate on the link between central and peripheral cardiovascular adaptations after continuous and intermittent training regimens differing in intensity.